2011
DOI: 10.1002/etc.619
|View full text |Cite
|
Sign up to set email alerts
|

Comparative toxicity of eight oil dispersants, Louisiana sweet crude oil (LSC), and chemically dispersed LSC to two aquatic test species

Abstract: The present study describes the acute toxicity of eight commercial oil dispersants, South Louisiana sweet crude oil (LSC), and chemically dispersed LSC. The approach used consistent test methodologies within a single laboratory in assessing the relative acute toxicity of the eight dispersants, including Corexit 9500A, the predominant dispersant applied during the DeepWater Horizon spill in the Gulf of Mexico. Static acute toxicity tests were performed using two Gulf of Mexico estuarine test species, the mysid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
124
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 180 publications
(134 citation statements)
references
References 12 publications
10
124
0
Order By: Relevance
“…The observed increase in toxicity associated with the uninoculated dispersed oil is consistent with the literature, and numerous studies have shown dispersant-oil mixtures to be significantly more toxic than dispersants alone (14,(19)(20)(21)62). Like Rico-Martínez et al (14), we saw a synergistic effect of Corexit 9500A, with Macondo crude oil increasing the toxicity to the marine rotifer B. manjavacas relative to Corexit alone or to physically dispersed crude oil.…”
Section: Figsupporting
confidence: 91%
See 1 more Smart Citation
“…The observed increase in toxicity associated with the uninoculated dispersed oil is consistent with the literature, and numerous studies have shown dispersant-oil mixtures to be significantly more toxic than dispersants alone (14,(19)(20)(21)62). Like Rico-Martínez et al (14), we saw a synergistic effect of Corexit 9500A, with Macondo crude oil increasing the toxicity to the marine rotifer B. manjavacas relative to Corexit alone or to physically dispersed crude oil.…”
Section: Figsupporting
confidence: 91%
“…Furthermore, the EPA required British Petroleum (BP) to assess the toxicity of dispersed oils using the Brachionus rotifer test following the DWH oil spill (18). In another study, Hemmer et al (19) showed that dispersant-crude oil mixtures were more toxic than dispersants alone to mysid shrimp (Americamysis bahia) and inland silverside fish (Menidia beryllina). Other studies observed that dispersed oil and dispersant constituents showed higher toxicity than crude oil alone in coral species (20,21).…”
mentioning
confidence: 99%
“…However, knowledge of dispersant toxicity is useful, as these compounds are regulated in part based on their toxicity to several estuarine model species, which may or may not be representative of gelatinous marine species. Indeed, the dispersant Corexit EC9500A in the present study was more toxic to M. leidyi than to a model estuarine crustacean, the mysid Americamysis bahia (48 h LC 50 = 38 mg l −1 , Hemmer et al 2011). Mortality studies with Corexit and other common coastal zooplankton such as the copepods Acartia tonsa (Avila et al 2010) and L. aestiva (Cohen et al 2014) reported LC 50 s similar to those found for M. leidyi.…”
Section: Discussionsupporting
confidence: 70%
“…Results indicate that none of the dispersants tested displayed biologically significant endocrine-disrupting activity (30); dispersants alone were less toxic than dispersant-oil mixtures. SLC oil alone was generally similarly toxic to both test species as dispersant-oil mixtures, and the toxicity of Corexit9500A was generally similar to the toxicities of other available dispersants (31).…”
Section: Should Oil Be Dispersed Chemically? How?mentioning
confidence: 77%